AUTHORITY OF THE WOMAN "BU NYAI" IN LEADING BUSTANUL ULUM ISLAMIC BOARDING SCHOOL IN LENTENG POREH SUMENEP - Nur muhammad Yahya (INNOVATIO: Journal for Religious Innovations Studies, 2023)
This study examines Nyai's power as head of the Bustanul Ulum Lenteng Poreh Sumenep Islamic boarding school. Women's lives are badly impacted in both the private and societal realms by the issue of women's ontology, defined as God's creation from a man's rib. Women in positions of knowledge and high social prestige, such as Nyai Ustadzah and Lecturers, are unaffected by this issue. Women's leadership abilities are questioned simultaneously as religious dogma lists women as number two. Thus, it casts doubt on the legitimacy of women. Consequently, a strategy is required as a direction for study. The author applies Max Weber's theory to determine Nyai's leading authority and power. Weber divides authority into three parts: namely, management that is traditional, charismatic, legal, and rational. Weber divides authority into three parts: namely, management that is traditional, charismatic, legal, and rational. According to Weber, formal authority based on an old tradition and the position of power based on that tradition is reasonable and deserves respect, thus seeing the old tradition that has developed in a society where Nyai Amaniah is the heir to the leadership of the Bustanul Ulum Islamic Boarding School who has the right to lead even if a woman is called a Nyai. Abstrak: Tulisan ini mengkaji tentang otoritas kepemimpinan ibu nyai di dalam memimpin pondok pesantren Bustanul Ulum Lenteng Poreh Sumenep. Masalah Ontologi perempuan yang digambarkan ciptaan Tuhan dari tulang rusuk laki-laki berdampak negatif terhadap kehidupan perempuan baik di wilayah privat maupun sosial. Masalah tersebut tidak banyak berpengaruh pada posisi perempuan yang memiliki keilmuan dan status sosial yang tinggi, seperti Nyai Ustadzah dan Dosen. Keraguan akan kompetensi kepemimpinan perempuan bersamaan dengan dogma agama yang menyebut perempuan secara eksplisit mahluk nomor dua. Sehingga memunculkan keraguan tentang kredibilitas perempuan. Maka perlu adanya pendekatan sebagai panduan analisis. Maka penulis menggunakan teori Max Weber untuk mengetahui otoritas dan kekuasaan Nyai sebagai pemimpin, Weber membagi otoritas tiga bagian: yaitu otoritas yang bersifat tradisional, kharismatik, legal rasional. menurut Weber otoritas tradisional berdasarkan tradisi lama serta kedudukan kekuasaan yang dilandasi tradisi itu adalah wajar dan patut dihormati, dengan demikian melihat tradisi lama yang berkembang di masyarakat bahwa Nyai Amaniah merupakan pewaris pimpinan Pondok Pesantren Bustanul Ulum yang berhak memimpin meskipun seorang perempuan yang disebut dengan Nyai. Kata Kunci: Otoritas Perempuan, Pemimpin pesantren.